Identifying the Most Probable Mammal Reservoir Hosts for Monkeypox Virus Based on Ecological Niche Comparisons - Curaudeau, Manon; Besombes, Camille; Nakouné, Emmanuel; Fontanet, Arnaud; Gessain, Antoine; Hassanin, Alexandre (Viruses, 2023)
Previous human cases or epidemics have suggested that Monkeypox virus (MPXV) can be transmitted through contact with animals of African rainforests. Although MPXV has been identified in many mammal species, most are likely secondary hosts, and the reservoir host has yet to be discovered. In this study, we provide the full list of African mammal genera (and species) in which MPXV was previously detected, and predict the geographic distributions of all species of these genera based on museum specimens and an ecological niche modelling (ENM) method. Then, we reconstruct the ecological niche of MPXV using georeferenced data on animal MPXV sequences and human index cases, and conduct overlap analyses with the ecological niches inferred for 99 mammal species, in order to identify the most probable animal reservoir. Our results show that the MPXV niche covers three African rainforests: the Congo Basin, and Upper and Lower Guinean forests. The four mammal species showing the best niche overlap with MPXV are all arboreal rodents, including three squirrels: Funisciurus anerythrus, Funisciurus pyrropus, Heliosciurus rufobrachium, and Graphiurus lorraineus. We conclude that the most probable MPXV reservoir is F. anerythrus based on two niche overlap metrics, the areas of higher probabilities of occurrence, and available data on MPXV detection.